DIKOTOMI KEILMUAN DALAM ISLAM ABAD PERTENGAHAN (Telaah Pemikiran Al-Ghazali dan Al-Zarnuji) - Farida Laila, St. Noer (Jurnal Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2016)
The present research was aimed at describing the dichotomous attitude ofÂ Muslim medieval ulama toward the development of religious and non-religious sciences. Based on a library study on the thought of Imam al-Ghazali in his Ihyaâ âulum al-din, as well as the thought of al-Zarnuji in his Taâlim almutaâallim, it was found that both ulama did not stcrikly differentiate the two sciences. Al-Ghazali saw the relation ofÂ the two sciences not in âconflictâ but âindependentâ one each other, while al-Zarnuji devided the sciences based on their possitive aspects for Muslimsâ religious life. Al-Zarnuji did not classify sciences as religious and non-religious.Kata Kunci: Dikotomi, Pemikiran Al-Ghazali, Al-Zarnuji